UNIT 9.2 Assessment of Cell Viability. Issue 1 (April 2013) - Johnson, Simon; Nguyen, Vy; Coder, David
Abstract: Cell viability may be judged by morphological changes or by changes in membrane permeability and/or physiological state inferred from the exclusion of certain dyes or the uptake and retention of others. This unit presents methods based on dye exclusion, esterase activity, and mitochondrial membrane potential, as well as protocols for determining the pre‐fixation viability of fixed cells either before or after fixation with amine‐reactive dyes suitable for a range of excitation wavelengths. Membrane‐impermeable dead cell and live cell dyes as well as dye‐exclusion procedures for microscopy are also included. Curr. Protoc. Cytom. 64:9.2.1‐9.2.26. © 2013 by John Wiley & Sons, Inc.